Conflict Management and Outcomes in Franchise Relationships: The Role of Regulation - Antia, Kersi D.; Zheng, Xu (Vivian); Frazier, Gary L. (Journal of Marketing Research, 2013)
Franchise relationships are prone to conflict. To safeguard the rights of individual franchisees, several states have legislated greater franchisor disclosure (registration law) ex ante and/or franchisor “termination for good cause” (relationship law) ex post. The impact of regulatory oversight on franchisor–franchisee conflict, however, remains unclear. Relying on agency theory arguments, the authors first assess the influence of the regulatory context, both by itself and in combination with the franchise ownership structure, on the incidence of litigated conflict. Conditional on litigation, they also predict the impact of franchise regulation on both the parties’ litigation initiation and resolution choices and the resulting outcomes. The authors test the hypotheses using a unique multisource archival database of 411 instances of litigation across 75 franchise systems observed over 17 years. The results indicate that the regulatory context, by itself as well as in combination with the franchise ownership structure, significantly shapes parties’ conflict management choices. The authors also find evidence of a trade-off between prevailing in the particular conflict and achieving franchise system growth objectives.